Differential role of monocyte subsets in atherosclerosis - Hristov, Mihail; Weber, Christian (Thrombosis and Haemostasis, 2011)
Endothelial dysfunction and inflammation of the arterial wall continuously drive the development of atherosclerosis. Details regarding the sequential involvement of different monocyte subsets in the pathology of this disease have recently emerged. This review concentrates on major monocyte subpopulations in mouse and men and specifically addresses their phenotype, function and recruitment during primary atherosclerosis as well as their contribution to angiogenesis and tissue regeneration secondary to plaque rupture.
Keywords: Atherosclerosis; chemokines; monocytes